The Myosin5‐mediated actomyosin motility system is required for Verticillium pathogenesis of cotton. (10th April 2018) - Feng, Zhidi; Tian, Juan; Han, Libo; Geng, Yuan; Sun, Jie; Kong, Zhaosheng
Summary: The vascular wilt fungus Verticillium dahliae is one of the most destructive pathogens of cotton ( Gossypium hirsutum ) and many other economically important dicot plants. Fungal pathogens require Myosin‐mediated actomyosin motility system for colonization of their host plants; however, the mechanisms underlying this process have not been fully characterized for V. dahliae . Here, in a knock‐out experiment, we characterized the role of VdMyo5, a member of the Myosin V family, before and during infection of cotton and Arabidopsis thaliana . The VdMyo5 deletion mutant (ΔVdmyo5 ) fungi showed obvious defects in the development of conidia and the polarized elongation of vegetative hyphae, but no inhibition of host root penetration. Overall, the ΔVdmyo5 fungi exhibited dramatically reduced virulence in cotton and Arabidopsis, with almost no colonization in sections of host vascular tissue. We found labelled Myosin5‐GFP to be specifically enriched at the hyphal tip, co‐localized with FM4‐64 labelled Spitzenkörper, which is the vesicle supply centre in filamentous fungi. Comparative secretome analysis revealed that proteins associated with cell wall modification and degradation of reactive oxygen species were significantly altered in mutant strains. Our results indicate that Myosin5 is required for vegetative growth and full virulence, possibly by regulating vesicle transport. The findings provide important insight into the cellular mechanisms of Verticillium pathogenesis.